2016
DOI: 10.1038/srep23634
|View full text |Cite
|
Sign up to set email alerts
|

3D-QSAR and docking studies of flavonoids as potent Escherichia coli inhibitors

Abstract: Flavonoids are potential antibacterial agents. However, key substituents and mechanism for their antibacterial activity have not been fully investigated. The quantitative structure-activity relationship (QSAR) and molecular docking of flavonoids relating to potent anti-Escherichia coli agents were investigated. Comparative molecular field analysis (CoMFA) and comparative molecular similarity indices analysis (CoMSIA) were developed by using the pIC50 values of flavonoids. The cross-validated coefficient (q2) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 46 publications
3
53
0
Order By: Relevance
“…In fact, QSAR played an indispensable role in GPCR subtype selective ligand design1415, e.g., ARs16, dopamine receptors17, serotonin receptors 5HT1E/5HT1F18 and cannabinoid receptor CB1/CB21920. For AR ligands, Michelan et al .…”
mentioning
confidence: 99%
“…In fact, QSAR played an indispensable role in GPCR subtype selective ligand design1415, e.g., ARs16, dopamine receptors17, serotonin receptors 5HT1E/5HT1F18 and cannabinoid receptor CB1/CB21920. For AR ligands, Michelan et al .…”
mentioning
confidence: 99%
“…These characteristics favor increased membrane fluidity in the bacterial cell (Tsuchiya and Iinuma, 2000; Wu et al, 2013). In a recent study using a structure-activity relationship model, flavonoids were shown to affect Escherichia coli viability by damaging its outer membrane (Fang et al, 2016). Considering the high hydrophobicity of both flavonoids and the P. aeruginosa cell wall, it is possible that SF32-33 has an effect on P. aeruginosa viability and growth due to a strong hydrophobic interaction.…”
Section: Discussionmentioning
confidence: 99%
“…A docking study was performed for the tested compounds 2a, 2b, 2d, and 2e in order to scrutinize their possible interactions with gyrase B (GyrB43) from E. coli (PDB code: 4PRV; resolution 2.00 Å) by employing the docking module that was implemented in the MOE software. The bacterial DNA gyrase has been reported as a good target for antibacterial agents and the assessment of potential antibacterial activity of new compounds [18]. Figure 9 presents the best docking poses for the novel flavanone bearing chromene moiety inside the GyrB binding pocket.…”
Section: Docking Studiesmentioning
confidence: 99%
“…The overexpression of the cyclin-dependent kinase-2 (CDK2) has been documented in various categories of human tumors [12][13][14][15][16][17]. Molecular docking evaluations have been executed to acquire an additional comprehension of the binding behavior of the generated molecules with CDK2 (Protein Data Bank (PDB) ID: 1FVV) as well as gyrase B (GyrB43) from Escherichia coli (PDB code: 4PRV), which has been reported to be a target for analyzing antibacterial activities [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation